A Comprehensive Review of Collaborative Learning Approaches in General Education - Gusma Afriani; Nurul Zaman (Global Education Journal, 2026)
Collaborative learning has become an essential pedagogical approach in modern education, emphasizing active participation, shared responsibility, and social interaction among learners. However, despite its theoretical promise, its application in general education remains inconsistent and often limited to superficial group work. This study aims to provide a comprehensive understanding of collaborative learning approaches in general education by systematically reviewing empirical and conceptual studies published between 2010 and 2025. Using a systematic literature review method, data were collected from reputable databases such as Scopus, ERIC, and ScienceDirect, and analyzed through thematic content analysis. The results reveal that collaborative learning effectively enhances students’ cognitive, social, and emotional development when guided by well-structured pedagogy, teacher facilitation, and supportive classroom culture. The findings also highlight challenges in assessment, teacher readiness, and cultural adaptation, particularly in non-Western educational contexts. It concludes that collaborative learning, when grounded in constructivist and socio-cultural theories, holds significant potential to transform general education into an inclusive and student-centered learning environment. This study contributes by offering theoretical integration, practical insights, and recommendations for developing context-sensitive and equitable collaborative learning models.